2011
DOI: 10.4103/0974-8490.79110
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of Ocimum sanctum alcoholic leaf extract against paracetamol-induced liver damage in Albino rats

Abstract: Background:There is a lack of reliable hepatoprotective drugs in modern medicine to prevent and treat drug-induced liver damage. Leaves of Sacred/Holy Basil, i.e. Green Tulsi (Ocimum sanctum), belonging to family Lamiaceae are used traditionally for their hepatoprotective effect. We wanted to evaluate the hepatoprotective activity of Ocimum sanctum and observe whether synergistic hepatoprotection exists with silymarin.Materials and Methods:Albino rats (150–200 g) were divided into five groups. Groups A and B w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 7 publications
0
51
0
3
Order By: Relevance
“…The OS alcoholic leaf extract shows significant hepatoprotective activity [68] and synergism with silymarin. In liver, EO and extracts of OS could prevent oxidative stress by increasing glutathione peroxidae and catalase and were also effective in prevention of hepatic steatosis.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The OS alcoholic leaf extract shows significant hepatoprotective activity [68] and synergism with silymarin. In liver, EO and extracts of OS could prevent oxidative stress by increasing glutathione peroxidae and catalase and were also effective in prevention of hepatic steatosis.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…In liver, EO and extracts of OS could prevent oxidative stress by increasing glutathione peroxidae and catalase and were also effective in prevention of hepatic steatosis. [9,68] Its major biochemically active constituents such as eugenol, carvacrol, ursolic acid (UA), β-caryophyllene and rosmarinic acid showed anti-inflammatory, gastric and hepatoprotective properties. [25] OS L. The oil possesses anti-inflammatory activity due to dual inhibition of arachidonate metabolism supplemented by antihistaminic activity.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Despite remarkable advances in modern medicine, hepatic disease remains a worldwide health problem; thus the search for new medicines is still ongoing [7] . Plant and natural products have been used in traditional remedies worldwide for the prevention and treatment of liver diseases and much scientific research is needed to support such claims [8] . However, to the best of our knowledge, the hepatoprotective effect of C. ternatea flower, against acetaminophen-induced liver injury in mice has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Biometry Research Unit, Indian Statistical Institute, 203 revealed that cold water extract of Tulsi plant produced hepatotonic effect against Paracetamol and Carbon tetrachloride when albino rats fed orally for 6 days with Tulsi extract [53]. When Tulsi extract is used as adjunct with silymarin it show significant hepatoprotective effect [54].…”
Section: Hepatoprotective Activitymentioning
confidence: 99%